Enhancing MSME Performance through Entrepreneurial Orientation and Product Innovation: The Mediating Role of Competitive Advantage - Wahyu Fatma Niadi; Wijayanti Wijayanti (BALANCE: Economic, Business, Management and Accounting Journal, 2026)
The competitiveness and performance of MSMEs remain suboptimal, despite their significant role in the economy. Specifically, this difference arises from the suboptimal implementation of product innovation and entrepreneurial spirit. To address this issue, this study aims to determine the relationships among product innovation, entrepreneurial orientation, and the performance of Micro, Small, and Medium Enterprises (MSMEs), while considering competitive advantage as a mediating factor. An examination of 60 craft MSMEs in Magelang Regency was conducted using SmartPLS 4.0 and Partial Least Squares (PLS) software. The findings indicate that product innovation and an entrepreneurial mindset significantly improve MSME performance, both directly and indirectly through the utilization of competitive advantage. This insight underscores that a stronger entrepreneurial orientation and continuous product innovation can enhance competitive advantage, thereby improving overall performance. This research not only has academic value but also provides valuable suggestions for policymakers and MSME actors